A DIFFERENCE IN INCIDENCE OF VISUAL THREATENING DIABETIC RETINOPATHY BETWEEN PATIENTS WITH AND WITHOUT IMPAIRED SLEEP QUALITY - Lucky Fitrada; Nina Ratnaningsih; Erwin Iskandar (Indonesian Vitreoretinal Society, 2022)
Background: Diabetic retinopathy (DR) is a common and major complication of diabetes mellitus (DM), and is the leading cause of preventable blindness in adults of productive age after cataracts. The global prevalence of DR is 34.6% , consisting of proliferative diabetic retinopathy (7.0%), diabetic macular edema (6.8%), and visual threatening diabetic retinopathy (VTDR) (10.2%.) The risk factors for VTDR are age, duration of diabetes, glycemic control, hypertension, obesity, HbAIC levels, and dyslipidemia. In addition, impaired sleep quality is also indicated to be connected with the incidence of VTDR. Objective: To compare the incidence of VTDR between patients with and without impaired sleep quality. Methods: This was a cross-sectional comparative analytic observational study involving 178 type 2 diabetes mellitus patients with DR at the National Eye Center of Cicendo Eye Hospital who met the inclusion criteria. Subject characteristic data were taken from medical records and sleep quality data were collected through a structured interview using the Indonesian version of the Shorten Pittsburgh Sleep Quality Index (PSQI) questionnaire. Subjects were distributed into poor and good sleep quality groups. The presence of VTDR was then assessed. The differences were then analyzed statistically using chi-square test with a p value of 0.05 considered statistically significant.Results: Results showed that 66.2% and 71.1% of patients in the poor and good quality sleep group suffered from VTDR, respectively (p> 0.05). Conclusion: There is no difference in VTDR incidence between patients in productive age with type 2 DM between those with and without impaired sleep quality.